2020
DOI: 10.3390/rs12233892
|View full text |Cite
|
Sign up to set email alerts
|

CNN-Based Tree Species Classification Using High Resolution RGB Image Data from Automated UAV Observations

Abstract: Data on the distribution of tree species are often requested by forest managers, inventory agencies, foresters as well as private and municipal forest owners. However, the automated detection of tree species based on passive remote sensing data from aerial surveys is still not sufficiently developed to achieve reliable results independent of the phenological stage, time of day, season, tree vitality and prevailing atmospheric conditions. Here, we introduce a novel tree species classification approach based on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(31 citation statements)
references
References 35 publications
1
24
0
Order By: Relevance
“…Vila‐Viçosa et al 2020); vegetation structure (Betbeder et al 2017); or soil moisture, texture, and salinity (Kim et al 2020). Finally, artificial intelligence, in particular deep learning, can boost these tasks through the exploitation of petabytes of remote sensing data, such as in the detection and counting of seedlings or adult crowns (Buters et al 2019; Albuquerque et al 2020), the identification of tree species (Egli & Höpke 2020), and the detection of scattered trees (Brandt et al 2020; Guirado et al 2021) that could serve for postdisturbance regeneration. In summary, the fusion of remote sensing, ecological niche modeling, and artificial intelligence may help to identify the appropriate locations (e.g.…”
Section: Precision Forest Restorationmentioning
confidence: 99%
“…Vila‐Viçosa et al 2020); vegetation structure (Betbeder et al 2017); or soil moisture, texture, and salinity (Kim et al 2020). Finally, artificial intelligence, in particular deep learning, can boost these tasks through the exploitation of petabytes of remote sensing data, such as in the detection and counting of seedlings or adult crowns (Buters et al 2019; Albuquerque et al 2020), the identification of tree species (Egli & Höpke 2020), and the detection of scattered trees (Brandt et al 2020; Guirado et al 2021) that could serve for postdisturbance regeneration. In summary, the fusion of remote sensing, ecological niche modeling, and artificial intelligence may help to identify the appropriate locations (e.g.…”
Section: Precision Forest Restorationmentioning
confidence: 99%
“…As UAVs can be flexibly deployed and freely move in 3D space, the air-to-ground wireless channel (higher probability with LOS links) is usually better than the ground-to-ground counterpart [6]. Therefore, the UAV-assisted VANETs have great potential in improving the quality-of-service (QoS) vehicle-related applications [7].…”
Section: Introductionmentioning
confidence: 99%
“…Based on f k−1 and λ k−1 , we can solve the optimization problem P3 by the constraint relaxation scheme and the relax-and-rounding method. 7: until Obtain the feasible solution x * i,j . 8: repeat 9: According to the Lagrangian dual decomposition, we can solve the optimization problem P7 and P8.…”
mentioning
confidence: 99%
“…With the continuous development of deep learning, the segmentation and extraction of trees is also constantly improving. For the segmentation of 2D (Two-Dimensional) images, scholars have tended to use a convolutional neural network in deep learning [16][17][18] from traditional segmentation methods based on edge detection, threshold, region and specific theoretical tools. For example, Martins et al [19] segmented the trees in the urban environment image, Yan et al [20] identified different tree species and Chadwick et al [21] extracted the height of the crown of a single coniferous tree.…”
Section: Introductionmentioning
confidence: 99%